(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
Contemporary activities of both private and public sector enacts new methods and principles in terms of adapting to everyday market changes. Public sector organizations, including local self-government institutions, are challenged with new demands that are not always easily achieved. At such a time, the application of contemporary managerial concepts, such as New Public Management and Good Governance, are crucial for the efficiency and effectiveness of the public sector organizations. In transitional countries, and especially those that are candidates for accession to the European Union, such as Bosnia and Herzegovina, the most demanding criterion is public administration reform. That reform includes improvement of organizational and functional efficiency and effectiveness, reorganizing public administration from the state level to local self-government level, and improvement of public services. In this regard, the paper focuses on research of the efficiency of the public sector in Bosnia and Herzegovina and the countries of the Western Balkans, with focus on citizen satisfaction with certain public sector services. Citizen satisfaction with public services and public institutions can be considered as a direct outcome of government’s policy and activities. Also, citizen satisfaction survey results can reveal a lot on the issues of how governments function, both in terms of citizen actual experiences and their expectations. The paper presents the results of Western Balkans countries compared with the results of European Union countries in terms of health services, education, ease of doing business and e-government. Western Balkans countries do not have a sufficiently developed system for monitoring the satisfaction of public service users and harmonizing reform measures, and also they have not developed well a system of functional cooperation with private and civil sectors in order to improve the quality of public services and citizen satisfaction.